Plasmid-Mediated mcr-1 Colistin Resistance in Escherichia coli from a Black Kite in Russia - Tarabai, Hassan; Valcek, Adam; Jamborova, Ivana; Vazhov, Sergey V; Karyakin, Igor V; Raab, Rainer; Literak, Ivan; Dolejska, Monika (Antimicrobial agents and chemotherapy, 2019)
The gene mcr-1 conferring resistance to last-line antibiotic colistin has been reported globally. Here, we describe the first detection of plasmid-mediated colistin resistance in Russian wildlife, an isolate of Escherichia coli sequence type 2280 from a black kite (Milvus migrans) scavenging raptor. Whole-genome sequencing and plasmid transferability experiments revealed that mcr-1.1 was located on conjugative IncI2 plasmid pDR164 (59891 bp). Migratory black kites may contribute to the global spread of mobile colistin resistance.
Keywords: sekvenování celého genomu; Russia; kolistin; migrace zvířat; Plasmids; dravci; landfill; infekce vyvolané Escherichia coli; Animal Migration; Drug Resistance, Bacterial; antibakteriální látky; Microbial Sensitivity Tests; Escherichia coli Infections; colistin; Escherichia coli; Raptors; proteiny z Escherichia coli; Animals; DNA sequencing; Anti-Bacterial Agents; kite; wildlife; Escherichia coli Proteins; bakteriální léková rezistence; zvířata; plasmid; mikrobiální testy citlivosti; Rusko; plazmidy; Colistin; Whole Genome Sequencing